Kajian Konsentrasi Etanol dan Metode Ekstraksi Propolis dari Lebah Jenis Trigona sp. Terhadap Aktivitas Antimikroba Bakteri Escherichia coli dan Beberapa Karakteristik Ekstrak Propolis [Study of Ethanol Concentration, Propolis Extraction Method and Characteristics of Propolis extract of Trigona sp. bees to Antimicrobial Activity of Escherichia coli] - Vira Putri Yarlina (Jurnal Teknologi & Industri Hasil Pertanian, 2020)
Propolis is one of the natural products from Trigona sp. containing flavonoid compounds which have antimicrobial, antifungal, and antioxidant activity.  The purpose of this research was to determine the ethanol concentration, extraction methods, and characteristics of propolis extract that can inhibit the growth of Escherichia coli bacteria.  The method used was a randomized block design with 6 treatments in 3 replications. The treatments consisted of extraction methods and ethanol concentrations of 50%, 70%, and 90%.  The best results of this study were the extraction of propolis by the maceration method at 70% ethanol concentration. This propolis extract had a value of antimicrobial activity against Escherichia coli of 4.65 mm, brownish-black color, typical aroma of strong propolis, bitter taste, and had a minimum effective value of growing bacteria of 0.20% extract.